Long QT syndrome and left ventricular non-compaction in a family with KCNH2 mutation: A case report - Caiffa, Thomas; Tessitore, Antimo; Leoni, Loira; Reffo, Elena; Chicco, Daniela; D'Agata Mottolese, Biancamaria; Rubinato, Elisa; Girotto, Giorgia; Lenarduzzi, Stefania; Barbi, Egidio; Bobbo, Marco; Di Salvo, Giovanni (Frontiers in Pediatrics, 2022)
Background. Left ventricular noncompaction (LVNC) is an abnormality of the myocardium, characterized by prominent left ventricular trabeculae and deep inter-trabecular recesses. Long QT syndrome (LQTS) is a cardiac ion channelopathy presenting with a prolonged QT interval on resting electrocardiogram and is associated with increased susceptibility to sudden death. The association between LVNC and LQTS is uncommon. Case presentation. We report an Italian family with a novel pathogenic KCNH2 variant who presented with clinical features of LVNC and LQTS. The proband came to our attention after two syncopal episodes without prodromal symptoms. His ECG showed QTc prolongation and deep T wave inversion in anterior leads, and the echocardiogram fulfilled LVNC criteria. After that, also his sister was found to have LQTS and LVNC, while his father only presented LQTS. Conclusions. Physicians should be aware of the possible association between LVNC and LQTS. Even if this association is rare, patients with LVNC should be investigated for LQTS to prevent possible severe or even life-threatening arrhythmic episodes.